Electrochemical surface plasmon resonance based biosensor for α-fetoprotein detection via different coupling strategies - Bhawana Thakur; Amarnath Chellachamy Anbalagan; Pallavi Koyande; Shilpa N. Sawant (Scientific Reports)
Abstract Electrochemical surface plasmon resonance (ESPR) based biosensors play significant role in cancer detection due to its ability for real-time analysis and rapid detection. Herein, ESPR based biosensor was designed employing three different coupling strategies for the detection of cancer biomarker α-fetoprotein (AFP), a liver cancer biomarker. AFP antibody was immobilized on gold coated glass sensor disk using three different coupling strategies viz. (i) 1-Ethyl-3-[3-dimethylaminopropyl] carbodiimide / N-hydroxy succinamide (EDC/NHS), (ii) ethylene diamine/ glutaraldehyde (EDA/GA) and (iii) polyaniline/glutaraldehyde (PANI/GA) strategies. Among the three coupling strategies, immobilization via EDA/GA strategy afforded highest sensitivity (28°/(ng/ml)) with reasonable linear range (0.5-3 ng/ml) and whereas EDC/NHS strategy afforded wide linear range (5–70 ng/ml) with reasonable sensitivity (2.12°/(ng/ml). Immobilization efficiency and interaction steps involved in the sensor construction were investigated by electrochemical impedance spectroscopy. The sensor constructed using EDC/NHS strategy was validated by quantifying AFP in human blood serum samples, where the results are consistent with the values determined using ELISA. This fundamental study can help the researcher to choose the relevant coupling strategy for achieving desired sensor characteristics in clinical analysis of cancer biomarkers.